THE EFFECT OF ROSELLA DRIED CALYX INFUSION (HIBISCUS SABDARIFFA) IN LOWERING LDL CHOLESTEROL SERUM LEVEL ON CIGARETTE SMOKE EXPOSED MALE SPRAGUE DAWLEY RATS - Gabriela Rolanda; Lusiana Batubara; Indah Saraswati; Kusmiyati Tjahjono DK (Jurnal Kedokteran Diponegoro, 2022)
Background: Cigarettes increase cardiovascular risks by modifying lipid profiles through oxidation, alternating lipoprotein composition, and fat metabolizing enzyme activity. Vascular dysfunction can primarily identified by LDL cholesterol composition shift, one of atherosclerosis predictor. Rosella is a multifunctional herb that widely used as a pleasant tea. Aside from its rich components, anthocyanin, pectin, PCA and hibiscus acid are playing the role keys in lowering LDL cholesterol through lipid metabolism enzyme activity modification. Rosella is easy to find, relatively cheap, tasteful and also categorized as food-grade FDA approved.